How the Reactive End Group of Macro‐RAFT Agent Affects RAFT‐Mediated Emulsion Polymerization‐Induced Self‐Assembly. Issue 19 (4th July 2021) - Cao, Junpeng; Tan, Yingxin; Chen, Ying; Zhang, Li; Tan, Jianbo
Abstract: Polymerization‐induced self‐assembly via reversible addition‐fragmentation chain transfer (RAFT)‐mediated emulsion polymerization is an emerging method in which macro‐RAFT agents are chain extended with hydrophobic monomers in water to form block copolymer nano‐objects. However, almost all RAFT‐mediated emulsion polymerizations are limited to AB diblock copolymers by using monofunctional macro‐RAFT agents with non‐reactive end groups. In this study, the first investigation on how the reactive end group of macro‐RAFT agent affects RAFT‐mediated emulsion polymerization is reported. Three macro‐RAFT agents with different end groups are synthesized and employed in RAFT‐mediated emulsion polymerization. Effects of end groups on morphologies of block copolymer nano‐objects and polymerization process are studied. Block copolymer nano‐objects prepared by using an asymmetric difunctional macro‐RAFT agent can be functionalized by further chain extension on the surface. It is expected that the current study will not only expand the scope of RAFT‐mediated emulsion polymerization, but also provide a novel strategy to prepare functional polymer nanoparticles. Abstract : The effect of the reactive end group of macro‐RAFT agent on aqueous RAFT‐mediated emulsion polymerization‐induced self‐assembly is investigated for the first time. Chain extension efficiency and morphologies of block copolymer nano‐objects can be easily tuned by changing the end group of macro‐RAFT agent.